ChemInform Abstract: Recent Developments in Alkyne Borylations. Issue 2 (January 2015) - Barbeyron, Renaud; Benedetti, Erica; Cossy, Janine; Vasseur, Jean‐Jacques; Arseniyadis, Stellios; Smietana, Michael
Abstract Review: [152 refs.